Efficacy of tirzepatide 5, 10 and 15 mg versus semaglutide 2 mg in patients with type 2 diabetes: An adjusted indirect treatment comparison. Issue 9 (13th June 2022) - Vadher, Karan; Patel, Hiren; Mody, Reema; Levine, Joshua A.; Hoog, Meredith; Cheng, Alice YY.; Pantalone, Kevin M.; Sapin, Hélène
Abstract: Aim: To conduct an adjusted indirect treatment comparison (aITC) of the efficacy of tirzepatide 5/10/15 mg versus semaglutide 2 mg in patients with type 2 diabetes. Materials and Methods: The primary analysis was a Bucher aITC of the change from baseline at week 40 in HbA1c (%) and body weight (kg). Aggregate data from the SURPASS‐2 study that met the HbA1c inclusion criterion of the SUSTAIN FORTE study and from SUSTAIN FORTE metformin‐only treated patients were used for primary analysis. Results: The SURPASS‐2 refined population comprised 238/245/240 and 240 participants for tirzepatide 5/10/15 mg and semaglutide 1 mg, respectively. The SUSTAIN FORTE metformin‐only population comprised 222 and 227 participants for semaglutide 1 and 2 mg, respectively. In this aITC, tirzepatide 10 and 15 mg significantly reduced HbA1c versus semaglutide 2 mg with an estimated treatment difference (ETD) of −0.36% (95% confidence interval [CI] −0.63, −0.09) and −0.4% (95% CI −0.67, −0.13), respectively. Tirzepatide 10 and 15 mg significantly reduced body weight versus semaglutide 2 mg with an ETD of −3.15 kg (95% CI −4.84, −1.46) and −5.15 kg (95% CI −6.85, −3.45), respectively. There were no significant differences between tirzepatide 5 mg and semaglutide 2 mg on change from baseline in HbA1c and body weight. Conclusions: In this aITC, HbA1c and weight reductions were significantly greater for tirzepatide 10 and 15 mg versus semaglutide 2 mg and were similar for tirzepatide 5 mg versus semaglutide 2 mg. These findings provide comparative effectiveness insights in the absence of a head‐to‐head clinical trial.